MicroRNA 21 is a homeostatic regulator of macrophage polarization and prevents prostaglandin E-2-mediated M2 generation - Wang, Zhuo; Brandt, Stephanie; Medeiros, Alexandra [UNESP]; Wang, Soujuan; Wu, Hao; Dent, Alexander; Serezani, C. Henrique (Public Library Science, 2015)
Macrophages dictate both initiation and resolution of inflammation. During acute inflammation classically activated macrophages (M1) predominate, and during the resolution phase alternative macrophages (M2) are dominant. The molecular mechanisms involved in macrophage polarization are understudied. MicroRNAs are differentially expressed in M1 and M2 macrophages that influence macrophage polarization. We identified a role of miR-21 in macrophage polarization, and found that cross-talk between miR-21 and the lipid mediator prostaglandin E-2 (PGE(2)) is a determining factor in macrophage polarization. miR-21 inhibition impairs expression of M2 signature genes but not M1 genes. PGE(2) and its downstream effectors PKA and Epac inhibit miR-21 expression and enhance expression of M2 genes, and this effect is more pronounced in miR-21-/-cells. Among potential targets involved in macrophage polarization, we found that STAT3 and SOCS1 were enhanced in miR-21-/-cells and further enhanced by PGE2. We found that STAT3 was a direct target of miR-21 in macrophages. Silencing the STAT3 gene abolished PGE(2)-mediated expression of M2 genes in miR-21-/-macrophages. These data shed light on the molecular brakes involved in homeostatic macrophage polarization and suggest new therapeutic strategies to prevent inflammatory responses.